Adaptation and Valorization of Entrepreneurship in Irrigated Agriculture: Nutrition Mainstreaming - AVENIR Project - Chege, Christine Gacheri Kiria; Nouwodjro, Kanté; Kane, Babacar; Mwongera, Caroline (2022)
Food and nutrition insecurity remain critical challenges in Senegal, aggravated by poor dietary diversity, yearly hunger seasons, and food safety challenges, especially concerning water, sanitation, and hygiene. One of the goals of the Adaptation and Valorization of Entrepreneurship in Irrigated Agriculture (AVENIR) project is to improve diets and contribute to better nutrition of the households in the regions of Sedhiou and Tambacounda, Senegal. This will be achieved through improved food availability, accessibility, affordability, acceptability, and quality of diverse nutritious and safe foods. The project is promoting sustainable food consumption patterns in a gender-equitable manner while considering environmental, socio-cultural, and economic sustainability. In total, 6,750 people—70% women and 30% youth— will benefit from the nutrition interventions. Women of reproductive age, grandmothers, and youth will be targeted. Interventions will be implemented through community engagement and learning sessions. Nutrition is mainstreamed in the AVENIR project activities based on the ‘Do No Harm’ principle. This guide is created for AVENIR project implementers and partners and it is designed to highlight key information and expectations regarding nutrition mainstreaming in the project. It shows pathways for improving nutrition in AVENIR and how the different nutrition sensitive activities would lead to improved diets. This guide should be used by the project team in conjunction with nutrition mainstreaming trainings.